Internet and distributed computing systems : 7th International Conference, IDCS 2014, Calabria, Italy, September 22-24, 2014. Proceedings - Fatta, Giuseppe; Li, Wenfeng; Ochoa, Sergio; Cuzzocrea, Alfredo; Pathan, Mukaddim; Fortino, Giancarlo (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 7th International Conference on Internet and Distributed Computing Systems, IDCS 2014, held in Calabria, Italy, in September 2014. The 23 revised full and 15 revised short papers presented were carefully reviewed and selected from 50 submissions. The papers cover the following topics: ad-hoc and sensor networks; internet and Web technologies; network operations and management; multi-agent systems; cloud-based information infrastructures.